Technical and Economical Analysis of Power Management System for Electric and Hydrogen Vehicles Charging Station Using Solar Powered, Hydrogen and Fuel Cell Technology - Mohanraj, S.; Divyapriya, S.; Amudha, A.; Emayavaramban, G.; Viyathukattuva; Siva Ramkumar, M. (International Journal of Psychosocial Rehabilitation, 2019)
For a Hydrogen and Electric vehicles, a novel power management system (PMS) charging station using diesel energy battery bank (BB), conversion system (DECS) and photovoltaic (PV) with hydrogen unit(HYG) and fuel cell unit(FC) is proposed in this project. Proposed PMS system’s control objectives of are: (i) to ensure battery management based on irradiance condition of PV as well as Diesel generation capacity, Hydrogen level and Fuel cell capacity, (ii) to decrease system’s power loss (high efficient) (iii) to enhance the system reliability and power quality. In this project, we proposed the power management and stability improvement of a Electrical Vehicle connected system with a large-scale Diesel generator (DG)-photovoltaic (PV) and Fuel cell (FC) with hydrogen unit, an energy-storage unit based on battery is implemented. For hydrogen and electric vehicles, off-grid charging system is designed by this project. At same time, it is possible to charge, hydrogen and electric vehicles. On charging station, they appears like two hydrogen and electrical load demand. Solar panels are used to power charging station. An additional converter unit is implemented using bidirectional buck boost converter for battery, hydrogen and fuel cell unit used. With respect to grid’s reliability enhancement, minimization of loss, sharing of load, management of battery, for operating conditions, better operational performance is exhibited by proposed PMS method. MATLAB/SIMULINK environment is used for simulating proposed system.